First mutation in the FSHR cytoplasmic tail identified in a non-pregnant woman with spontaneous ovarian hyperstimulation syndrome - Justine Hugon-Rodin; Charlotte Sonigo; Anne Gompel; Catherine Dodé; Michael Grynberg; Nadine Binart; Isabelle Beau (BMC, 2017)
Abstract Background Spontaneous ovarian hyperstimulation syndrome (sOHSS) is a rare event occurring mostly during natural pregnancy. Among described etiologies, some activating mutations of FSH receptor (FSHR) have been identified. Case presentation We report hereby the case of a non-pregnant women with three episodes of sOHSS. Hormonal evaluation was normal and no pituitary adenoma was detected. However, genetic analysis identified a novel heterozygous FSHR mutation (c.1901 G > A). This R634H mutation is the first described in the cytoplasmic tail of the receptor. Functional analysis failed to reveal constitutive activity of the mutant but a decreased cAMP production in response to FSH. The weak activity of this mutant is correlated with a markedly reduced cell surface expression. Conclusion Pathophysiology of non gestationnal sOHSS is still ill established. The molecular characterization of this new mutant indicates that it might not be at play. Therefore, further investigations are needed to improve knowledge of the molecular mechanism of this syndrome.